SKOPJE - Schwartz, Jonathan (Tidsskriftet Antropologi, 2003)
The article explores some of the ways in which the citizens and officials of the Republic of Macedonia commemorated on July 26, 2003 the 40th anniversary of the earthquake that destroyed much of Skopje, the capital city of the Republic. The fragile Republic in the center of the Balkans also commemorated during the same week the 100th anniversary of the failed Ilinden uprising against Ottoman Turkish rule, August 2, 1903. The study aims at connecting diverse expressions of how a particular society remembers its disasters and attempts to turn them towards redemption. The Macedonian sociologist, Ilja Acheski, used the term “permanent earthquake” to describe the social fragmentation of his city in the aftermath of the 1963 earthquake. The article represents an extensive commentary on this theme. One of the characteristic responses during the earthquake memorial was nostalgic, perhaps “Jugonostalgic”. Several people stressed to the ethnographer how the world society – in the midst of the Cold War – cooperated to help Skopje during its moment of need. At the unveiling of a monumental sculpture of a suffering woman, who is meant to symbolize Skopje, an older man told me how America and Russia joined to help Skopje in 1963. The commemoration of Skopje’s earthquake, therefore, made it possible to acknowledge once again the personal leadership of Tito for his “Brotherhood and Unity” policy and for his skill at uniting East and West. Most of the article, however, does not dwell on the site of the monument. The author takes long walks in Topaana, a Roma “slum”, Cair, a neighboring Albanian “village”, and Lisece, a Macedonian “barracks” suburb. This last named site is one of the working-class suburbs where the wooden frame houses were built as contributions from abroad to rehouse the victims made homeless by the earthquake.